Evidence Based Medicine - Abstracts of Poster Presentations - Editor, The (Nepal Journal of Epidemiology, 2014)
Abstracts of the Poster Presentations at the session on Evidence Based Medicine at the International Conference on Research Methodology and Research Writing (ICRMSW) 2013. DOI: http://dx.doi.org/10.3126/nje.v4i2.10166